Responsabilidade subjetiva e objetiva no domínio da improbidade - Ebenau, Felipe Humberto Meneghello (2021)
This study deals with the topic of fault liability and strict liability in the Brazilian legal system of administrative dishonesty. It intends to investigate how the topic has been treated in the legal environment, in order to ascertain how, under which terms, and under which conditions, fault liability and strict liability give way to administrative dishonesty. Aspects related to “negligence” and “intent” modalities in the Law No. 8.429/1992 are addressed, as well as to what extent the subjective element influences the fault liability for the act of administrative dishonesty, in view of the intense legal discussion on the matter. Furthermore, the verification of accountability for an act of administrative dishonesty received a new focus, especially after the enactment of Law No. 12.846/2013, and was transposed to the strict liability field, which is part of the topic of the present work. Investigations of the differences between fault and strict liabilities as well as their nuances in the Brazilian legal system of accountability for acts of administrative dishonesty have revealed the following conclusion: Law No. 8.429/1992 cases are to be dealt with exclusively under the concept of fault liability, and correspondingly, cases of strict liability are exceptional and are to be dealt with only under the terms of the Law No. 12.846/2013